Factors influencing ethics of accountants in financial reporting - Jayatkomarunn, Subashini (2016)
Recently, studies show that financial reporting fraud is increasing in Malaysia and accountants are involved in the fraud. Financial reporting fraud is an unacceptable behavior and it needs to be combated. Ethics is an important component in the accounting profession. However, the ethics of accountants are still questionable due to the increase of ethical failure in financial reporting. The ethical failures have proved that accountants failed to act ethically in disclosing information’s in their financial statement. The reasons for accountant’s ethical failures are inappropriate ethical judgment, pressure from top management, lack of peers support, poor attitude, and having opportunities to involve in unethical conducts. Accountants are responsible to protect the public interest and public have the expectation that accountants need to act with integrity. However, the financial reporting fraud has caused public distrust of the accountants. This is because accountants have breached their responsibility in providing truthful financial information to the public. Hence, it is important to increase the ethics of accountants towards financial reporting. The objective of the research is to examine the influence of attitude, subjective norm, perceived behavioral control, and ethical judgment, towards ethical intention of accountants in their financial reporting. The second objective of the research is to investigate the influence of ethical intention towards the ethical behavior of accountants in their financial reporting. The third objective is to determine the whether ethical intention mediate the relationship between attitude, subjective norm, perceived behavioral control, ethical judgment and ethical behavior in financial reporting. Theory of Planned behavior (TPB) is used as an underlying theory in this research. Questionnaires were used to gather data from a sample of 133 Malaysian accountants, which indicates 53% of response rate. Using multiple regression analysis, the statistical technique, data were analyzed and the research hypotheses were tested. The overall findings of this research have shown that there is a positive relationship between attitude, perceived behavioral control, ethical judgment, and ethical intention of accountants in their financial reporting. However, the proposed direct influence of subjective norm was not supported. The ethical intentions positively influence accountant’s ethical behavior. The ethical intention fully mediates the relationship between attitude and perceived behavioral control. Besides, ethical intention partially mediates the ethical judgment and did not mediate the subjective norm. The findings of this research would be useful to increase accountant’s ethical decision making towards financial reporting. Results of the research present practical implications to accounting regulators and Ministry of Education to maximize the ethical decision making of the accountants by tapping the factors into their training programs, conferences, and ethics education. This research also contributes to the body of knowledge on factors influencing accountant’s ethical intention and their ethical behavior on financial reporting in the area of business ethics.